Pengaruh Kompetensi Manajerial Dan Supervisi Kepala Madrasah Terhadap Kinerja Guru Di MTsN Tulung Kecamatan Saradan Madiun - Sudjono; Muhtadi; Adibah Jauhari (Arsy : Jurnal Studi Islam, 2019)
Principals and teachers are the ones who was instrumental in determining the success of education in school. The success of a school is essentially lies in the efficiency and effectiveness of performance as someone who was given the task to lead the school. Principal is expected to be a leader and innovator in the School. Therefore, the quality Principal manajerial competence is significant to the success of the School. Principals as a manager and supervisor helped, encourage and give confidence to the teachers that teaching and learning can and should be improved. The development of a variety of experiences, knowledge, attitudes and skills of teachers should be conducted in a professional manner in accordance with the competence. The purpose of this research is to analysis influence manajerial competence, Supervision on Job performance among teachers in Islamic Yunior State School Of Tulung Saradan Madiun. The population and sample in this research is all the teachers in Islamic Yunior State School Of Tulung which is 18 teachers, because the population is less than 100 in its account, then the sample is taken from that population. Design of this research is quantitative research because testing relationship between three variable there is Manajerial competence, Supervision and Job performance. Collecting data methods using questionnaire which is given to all the teachers Islamic Yunior State School Of Tulung as the respondents than it is analyzed using pearson influence and proceed with 17th version of SPSS software. The results of this study indicate that: (1) there is a positive significant (p = 0,019) the influence manajerial competence on performance among teachers in Islamic Yunior State School Of Tulung Saradan Madiun (2) positive significant (p = 0,044) influence Supervision on Job performance among teachers in Islamic Yunior State School Of Tulung Saradan Madiun (3) positive significant (p = 0,000) simultanly influence manajerial competence and Supervision on Job performance among teachers in Islamic Yunior State School Of Tulung Saradan Madiun with Y = 5.222 + 0.380X1 + 0.513X2. Based on these results, the authors give advice to all teachers in MTs Negeri Tulung Saradan Madiun districts as much as possible in order to demonstrate competence and high performance in the Work of duty as teachers to provide role models for the students and the school community